Friends, Citizens, Strangers : Essays on Where We Belong - Vernon, Richard, 1945- (Book collections on Project MUSE., 2005)
Friends, Citizen, Strangers proposes a solution: a moderate form of cosmopolitanism that finds a place for multiple levels of attachment and association.